Prevalence of human pseudocholinesterase (butyrylcholinesterase) deficiency in central Anatolian people: A cross-sectional study - Gencer, Muzaffer; Göçmen, Yeşim (Journal of Surgery and Medicine, 2020)
Aim: Human pseudocholinesterase (PChE) is an enzyme responsible for hydrolysis of the muscle relaxant drugs like succinylcholine and mivacurium. PChE deficiency, which may lead to prolonged apnea, may occur due to hereditary or acquired causes. In our study, we aimed to investigate the prevalence of human pseudocholinesterase (PChE) enzyme deficiency around the central Anatolia region and present our results in light of the literature. Methods: This cross-sectional study included 936 patients (age 18-70 years) who underwent any elective surgery under general anesthesia between August 2015 and September 2019. Human PChE level, plasma PChE activity, the human PChE activity/albumin, serum liver and kidney function tests were analyzed from blood samples. Human PChE enzyme deficiency and possible association of the PChE deficiency with other values was also investigated. The normal value of PChE was considered to range from 4650 U/L to 10,440 U/L. Results: PChE activity was decreased in 19 (1.9%) of the 936 patients (442 males and 494 females). There was no statistically significant difference between the PChE levels in terms of gender (P=0.236). The mean human PChE activity of all patients was 7.490 (0.980). The PChE activity of 22 (2.35%) and 58 patients (6.4%) were below 5.000 U/ml and 6.000 U/, respectively. A statistically significant difference was found between serum urea, creatinine and human PChE levels (P=0.034, P=0.236, respectively). However, PChE deficiency had no correlation with liver function tests such as AST and ALT (P=0.432, P=0.022, respectively). Conclusion: PChE deficiency can be observed in preoperatively evaluated patients and may cause serious life-threatening conditions, including respiratory failure and prolonged apnea.